Simulated time-dependent climate response to solar radiative forcing since 1600 - Rind, D.; Lean, J.; Healy, R. (Journal of Geophysical Research-Atmospheres, 1999)
Estimated solar irradiance variations since 1500 have been used to force the GISS atmospheric GCM coupled to a mixed layer "q-flux" ocean with heat diffusion through the bottom of the mixed layer. The goal is to assess solar-induced climate change in preindustrial and postindustrial epochs. Six simulations and control runs were made to test the effects of different initial conditions, estimates of initial solar forcing conditions, and ocean heat uptake. The results show that an estimated solar forcing increase of 0.25% accounts for a 0.45 degrees C temperature increase since 1600 and an increase of about 0.2 degrees C over the past 100 years. Global surface temperatures lag solar fluctuations by up to 10 years; the lag is greater over the oceans and so is the correlation due to reduced noise. With only a mixed layer ocean the phase lag is 5 years less. Solar forcing and water vapor feedback each directly account for 35% of the temperature response, with cloud cover changes contributing 20% and sea ice/snow cover 10%. Uncertainty in the initial radiation imbalance or solar forcing affects the surface temperatures for 60-90 years. Modeled and observed periodicities show dominance of long-period forcing (>50 years), as provided by the solar input in these experiments. Tropical temperatures correlate best with solar forcing, due to the influence of water vapor feedback, especially at these multidecadal periods. Sea ice and extratropical temperatures have less long-period power, while high-frequency fluctuations dominate simulated cloud cover variations, which are relatively independent of solar forcing changes. Global and extratropical precipitation increase as the climate warms, but not low and subtropical precipitation, due to conflicting influences of absolute temperature and temperature gradient changes. Solar forcing by itself was not sufficient to produce the rapid warming during the last several decades. A comparison experiment varying trace gas forcing suggests that if the solar estimate is correct, then negative forcing by tropospheric aerosols (and perhaps volcanoes, ozone, and land use changes) has been about -1.2 W m(-)2 since 1700, implying approximately equal contribution from direct and indirect tropospheric aerosol effects.
id: 1945; PT: J; UT: WOS:000078242200003